Psychological Stress, Inflammation, and Coronary Heart Disease - Wirtz, Petra H.; von Känel, Roland (My University, 2017)
Purpose of Review
In this review, we summarize evidence on the risk factor psychological stress in the context of coronary heart disease (CHD) in humans and explore the role of inflammation as a potential underlying mechanism.
Recent Findings
While chronic stress increases the risk of incident CHD and poor cardiovascular prognosis, acute emotional stress can trigger acute CHD events in vulnerable patients. Evidence supporting a potential role for inflammation as a promising biological mechanism comes from population-based studies showing associations between chronic stress and increased inflammation. Similarly, experimental studies demonstrate acute stress-induced increases in inflammatory markers and suggest modulatory potential for pharmacological and biobehavioral interventions. So far, studies investigating patients with cardiovascular disease are few and the full sequence of events from stress to inflammation to CHD remains to be established.
Summary
Psychological stress is an independent CHD risk factor associated with increased inflammation. Although promising, causality needs to be further explored.
Keywords: Psychosocial stress, Inflammation, Coronary heart disease, Cytokines, C-reactive protein, Interleukin, Inflammatory stress response, Intervention, Job burnout, Exhaustion; 150